2014
DOI: 10.1590/0104-07072014002010013
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal relationships among hospital nurses and the use of communication skills

Abstract: ABSTRACT:A qualitative exploratory and descriptive study investigating how the work relationships of nursing professionals are affected by the organizational problems experienced in hospital units and their management. Participants consisted of 21 nurses who worked in a general hospital in the north of Spain, during the period between 2010 and 2012. The study was approved by an ethics research committee and participants signed an informed consent form. Data were collected through in-depth interviews and field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
2
5
1
1
Order By: Relevance
“…Overall, factors found in the study also support the findings of prior research that money or financial incentives are not the only factors important for HCP motivation in other low and middle income countries [11, 14, 64, 65]. Poor working conditions and the quality of care provided to patients can also greatly affect job satisfaction [25, 66]. A lack of appropriate resources can also lead to frustration and demotivation due to compromised health care quality, which can occur despite the intentions or capabilities of health providers [19, 52, 67].…”
Section: Discussionsupporting
confidence: 84%
“…Overall, factors found in the study also support the findings of prior research that money or financial incentives are not the only factors important for HCP motivation in other low and middle income countries [11, 14, 64, 65]. Poor working conditions and the quality of care provided to patients can also greatly affect job satisfaction [25, 66]. A lack of appropriate resources can also lead to frustration and demotivation due to compromised health care quality, which can occur despite the intentions or capabilities of health providers [19, 52, 67].…”
Section: Discussionsupporting
confidence: 84%
“…The results of this study showed correlation between the personality dimensions of extroversion, pleasantness, and responsibility and communication skills; thus, they contradict the findings of the studies by Kuntze et al and Smith et al (45,46). Perhaps, in addition to intrapersonal issues such as personality, issues such as teaching effective communication (47), regional culture (10), patient's behavior (48), and intraorganizational issues (3,49) are also important in this regard. Getting the best and fastest health care with maximum safety is the right of every human being (50) and the nurse is at the forefront of providing these services in hospitals.…”
Section: Discussioncontrasting
confidence: 82%
“… 25 Communication between nurses and co-workers, in conjunction with good, interpersonal relationships and social interaction, is considered indispensable conditions for feeling comfortable with one’s work. 26 …”
Section: Discussionmentioning
confidence: 99%